If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17x + 19 = 23 Reorder the terms: 19 + 17x = 23 Solving 19 + 17x = 23 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-19' to each side of the equation. 19 + -19 + 17x = 23 + -19 Combine like terms: 19 + -19 = 0 0 + 17x = 23 + -19 17x = 23 + -19 Combine like terms: 23 + -19 = 4 17x = 4 Divide each side by '17'. x = 0.2352941176 Simplifying x = 0.2352941176
| 8(-2a-5)+6=-82 | | Cot=30 | | 5x+y=192 | | x-5=-x-4 | | 3*x^2-17=0 | | 11-3p=-64 | | (-5xy)(x^2y)(3y)= | | 2/3(12y-15) | | 17+90+x=180whatsx | | 0.5x+x=4.5 | | 22+140+x=180whatsx | | log[5](2x+6)=1 | | -89=-5p-4 | | 3X*2-17=0 | | 3/7*28= | | 3(6+-s)+2s=6 | | x-8/9=-11-x/8 | | 5x+11y=558 | | 40=-8+2m | | -29=5(2a-1)+a | | 15-x=3+3x | | y^2+xy+8=0 | | 5+y-2=6 | | 5x^2-17=-19 | | 2f(5)-f(4)= | | 5+y-2=8 | | 2(w+6)-6w= | | 5+x-2=3 | | (3y-7)+(2y-2)= | | 7(x+9)+x=4(x+4)-4 | | 6+6(x-1)=3+12x | | -4(k+7)=-34-3k |